IMPROVING BASIC DRIBLING TECHNIQUES IN SOCCER GAMES THROUGH ZIG-ZAG RUN EXERCISES - Cepriyana, Cepriyana; Suherman, Ayi; Mulyanto, Respaty (Riyadhoh : Jurnal Pendidikan Olahraga, 2024)
This research aims to improve football learning outcomes in basic dribbling techniques for class IV students at SDN Gununglarang 1, Majalengka Regency, through zig-zag run training. Obtain information about the implementation of the Basic Dribbling Technique of Football Learning using a zig-zag run for class LV students at SDN Gununglarang 1, Majalengka Regency. This research uses the action research method (Action Research) using the Kemmis and Mc. Taggart model research design in the form of a cycle. Apart from that, action research was carried out to obtain information about the action and application of zig-zag runs in football games to improve basic dribbling movements in fourth-grade elementary school students. The results of cycle research I, the average value of the class learning outcomes for basic soccer dribbling techniques was 7.0 with a completion percentage of 73% of students who passed, and seen from the student learning outcomes in cycle II it was 8.0 with a completion percentage of 85% of students who passed The results of the initial test and final test of the research with a sample size of 26 students achieved an increase of 85% or more than 80%. From the results of this research, it can be concluded that Zig-Zag Run can improve learning outcomes for basic soccer dribbling techniques. This research concludes that learning basic dribbling techniques in football with Zig-zag Run can improve the basic dribbling movements of class IV students at SDN Gununglarang, Majalengka Regency